Incentives-adoption-food security: Implications for sustainable cocoa production in Ghana. - Tham-Agyekum, Enoch Kwame; Ankuyi, Fred; Bakang, John-Eudes Andivi; Mensah, Jonathan; Nimoh, Fred; Adarkwa, Bright Oteng; Ankrah, Daniel (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
This study investigates the adoption of the Cocoa Rehabilitation Programme (CRP), aiming to understand the factors influencing farmers' participation and assess the impact on food security. The research gathered quantitative data from 385 cocoa farmers in the Osino Cocoa District, Eastern region, Ghana. Mean, frequency, Tobit and ordered logit regression models were used to analyse the data. Results reveal that incentives like farm maintenance without a charge, extension access, monetary rewards regular farm monitoring and free tree-cutting strongly promote CRP adoption. Gender, age, education, and various incentives significantly influence adoption levels. The study revealed that practices like weedicide-free farming, zero burning, and efficient shade management play a substantial role in improving the food security of farmers. The paper contributes to existing literature by offering a comprehensive analysis of both monetary and non-monetary incentives, adoption patterns, and outcomes, particularly regarding food security in the context of cocoa production. The study suggests a multifaceted approach to enhance CRP efficacy and address the complex dynamics of sustainable agricultural initiatives.